L’intercession (shafāʻa) sous les Omeyyades d’al-Andalus à travers quelques récits historiques - Omayra Herrero (Revue des Mondes Musulmans et de la Méditerranée)
Based on examples selected from historical chronicles and biographical dictionaries, this article attempts to identify the most propitious conditions for political intercession under the Umayyads of al-Andalus. Required in several prophetic traditions as well as in Qur’anic verses, intercession was also restricted by the Islamic tradition. Analyzing situations of conciliation (people concerned, loyalty networks), we can identify those who were most able to influence a sovereign’s decisions for application of his coercive power. Intercession by a member of a ruler’s inner circle, a possessor of rank (jāh), was generally successful. Finally, it appears that intercession was sometimes accomplished in situations where it was expressly prohibited by textual sources, as in the case of sacrilegious offences.